1998
DOI: 10.1002/(sici)1521-4141(199809)28:09<2780::aid-immu2780>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

IL-4 is a differentiation factor for transforming growth factor-β secreting Th3 cells and oral administration of IL-4 enhances oral tolerance in experimental allergic encephalomyelitis

Abstract: We have previously shown that following oral administration of myelin basic protein (MBP), regulatory T cells are generated from gut-associated lymphoid tissue and that these cells suppress experimental allergic encephalomyelitis (EAE). These regulatory T cells produce transforming growth factor-beta (TGF-beta) with various amounts of IL-4 and IL-10 and these TGF-beta-secreting T cells have been termed Th3 cells. T cells in lymphoid organs drained by mucosal sites secrete IL-4 as a primary T cell growth factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
97
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 202 publications
(104 citation statements)
references
References 36 publications
6
97
0
1
Order By: Relevance
“…Here, we show that during the induction of systemic tolerance after Ag inoculation into the eye, IL-10 mRNA and protein is selectively up-regulated and is absolutely required for the development of active suppression. Thus, although IL-4 is the cytokine usually associated with down-regulation of inflammation (66) and induction of Th3 Tr cells in oral tolerance (67), during the development of eye-induced active suppression, NK T-derived IL-10 is the major player.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we show that during the induction of systemic tolerance after Ag inoculation into the eye, IL-10 mRNA and protein is selectively up-regulated and is absolutely required for the development of active suppression. Thus, although IL-4 is the cytokine usually associated with down-regulation of inflammation (66) and induction of Th3 Tr cells in oral tolerance (67), during the development of eye-induced active suppression, NK T-derived IL-10 is the major player.…”
Section: Discussionmentioning
confidence: 99%
“…For immunohistochemistry, cryostat sections (5 m) of the aortic arch were cut, air-dried, fixed in acetone, and stained with anti-MAC-3 for macrophages, anti-CD4 for T cells, and anti-IL-10 (Pharmingen), anti-IFN-␥, and anti-TGF-␤ (R&D) for cytokine staining, as described. 15 Areas that stained positively for macrophages were measured by use of computer-assisted image quantification (IPLAB Spectrum P, 3.1). Lymphocytes identified by anti-CD4 or anti-cytokine antibody staining were counted microscopically by 4 observers blinded to the study protocol.…”
Section: See P 1599mentioning
confidence: 99%
“…30,31 High doses of oral or mucosal antigen lead to T cell receptor activation without costimulation and the simultaneous presence of inhibitory ligands leads to anergy 32 or deletion. 16,33 Low-dose tolerance is induced by regulatory cells, such as Th3, 18,19 T regulatory 1 cells 34,35 and CD4 1 CD25 1 regulatory cells. 36,37 Also, CD8 1 T cells, via the production of TGF-b, 38,39 and c/d T cells 40 have been identified as acting as regulatory cells during oral tolerance induction.…”
Section: Antigen Dose and Formulationmentioning
confidence: 99%
“…112 Many animal studies have reported that immune therapy for allergic diseases could be given by oral administration of OVA or purified allergens. [113][114][115] In addition to the adjustment of antigen dose and the frequency of dosing 116 for the mucosal adjuvants, including CTB, CpG ODNs and chitosan as previously mentioned, oral tolerance is enhanced by IL-4, 19 19,116,117 anti-IL-12, 118 TGF-â, 119 Flt-3 ligand 120 and anti-CD40 ligand. 121 Antigen absorption following oral administration is less dangerous in regards to the airways or skin, which suggests that the mouth is likely to be a tolerogenic site.…”
Section: Oralmentioning
confidence: 99%
See 1 more Smart Citation